PENGARUH JENIS GARAM KALSIUM DAN LAMA PENYIMPANAN TERHADAP KARAKTERISTIK SUKADE LAPISAN ENDODERMIS KULIT BUAH MELON (CUCUMIS MELO L) - Ratnasari, Lidya; Ristiarini, Susana; Widoeri, Theresia Endang (Jurnal Teknologi Pangan dan Gizi, 2012)
The usage of endodermic layers of melon (Cucumis melo L) to make succade have texture limitation. Blanching as a part of succade processing can make collapse texture of succade. To limitation the collapse texture need need soaking in firming agent solution like CaCl2, Ca(OH)2 and CaC6H10O6.5H2O. The usage of different calcium salt types will produce hygroscopicity differences which have effect to succade characteristic during storage. The experimental design is Nested Factorial Block Design. These are consist of two factors, the storage period (0, 1, 2, 3, 4 and 5 weeks) nested in the types of calcium salts (CaCl2, CaC6H10O6.5H2O and Ca(OH)2). Each treatment will be repeated three-times and tested parameter are water content, hardness, colour and organoleptic test (different test .i.e. performance, crispness and toughness). The data which obtained were analyzed with ANOVA (Analysis of Varians) at α = 5% then followed by Duncan’s Multiple Range Test at α = 5% to find the degree of treatment which was really different. The experiment showed that calcium salts types influence the water content and shrinkage degree, whereas storage period of each calcium salts types influence the water content, hardness, colour (lightness, yellowness and redness) and organoleptic (crispness and white patch). Succade which were soaked in CaCl2 or calcium lactate solution showed the increasing of water content during five weeks storage, which cause the increasing of tenderness, lightness, yellowness and decreasing of redness, crispness and white patch. Succade which soaked in Ca(OH)2 solution during five weeks storage showed insignificant of increased water content and decreasing of water content in second week which result the increasing of hardness, redness, white patch and decreasing of lightness and yellowness.